The illuminist discourse of the digital divide: a critic to the Post-Fordist Informatic Mundaneum from Knoxville, Tennessee - Berrio-Zapata, Cristian [UNESP]; Pomim Valetim, Marta Ligia [UNESP]; Goncalves Santana, Ricardo Cesar [UNESP]; Hernandez Humana, Ivan Dario (Univ Federal Campina Grande, 2015)
This article discusses the project of the Information Society and the discourses that undergo it, as part of a political and ideological conception universalized by those countries that created and dominate computer technology, which is in turn is aligned with the Post-Fordist industrial capitalist order and its emphasis on economic accumulation and consumerism. We explain how information technology creates routines and legitimate social orders, taking for analyzes the case of the Clinton-Gore policy in the United States, when the discourse of the computer society was associated with the development and social welfare. This association is revealed in the speech made by Clinton in the city of Knoxville in year 1996. There we see the beginnings of the concern about the Digital Divide as a new form of "social disease" that prevents the passage to a better world, focused on productivity, accumulation and consumption in information-dense societies. This generates a clash between the industrial-graph-centric world and the oral-pre-industrial communities, as a result of attempting to transplant the institutional forms of the developed West. We explain the pillars of the new computerized order, and how they replaced previous epic narratives creating techno-deterministic or techno-phobic discourses in prejudice of more critical approaches. We identify the effects such deterministic discourses that connote the association between the Information Society, welfare and development, questioning the urgency of deploying this system at global level without profound critical discussion, clear goals focused on the benefit of the human beings, and the open participation of the users of the system.

Este artigo discute o projeto da Sociedade da Informação e os discursos que se alicerçam nele, como parte de uma concepção política e ideológica universalizada pelos países que criaram e dominam a tecnologia informática que, por sua vez, está alinhada à ordem industrial capitalista Pós-Fordista, assim como à ênfase na acumulação econômica e o consumismo comercial. Explica-se como a tecnologia da informação cria rotinas e legitima ordens sociais, analisando como durante o mandato de Bill Clinton nos EUA, o discurso da sociedade informatizada conotou sua associação com o desenvolvimento e o bem estar social. Esta associação é revelada no discurso feito por Clinton na cidade de Knoxville no ano 1996. Ali é semeada a preocupação sobre a Brecha Digital como uma nova forma de “doença social” que impede a passagem para um mundo melhor, centrado na produtividade, a acumulação e o consumo em sociedades informacionalmente densas. Surge um choque entre o mundo grafocêntrico- industrial e as comunidades orais pré-industriais por conta da tentativa de transplantar as formas institucionais do ocidente desenvolvido. Os pilares da nova ordem mundial informatizada são explanados assim como eles substituem as narrativas épicas anteriores, gerando discursos tecno-deterministas ou tecno-fóbicos em prejuízo de abordagens críticos. No final, se identificam os efeitos dos discursos deterministas que conotam a associação entre a Sociedade da Informação, bem estar e desenvolvimento, questionando a urgência de implantar este regime a nível global sem que exista uma discussão critica profunda, alvos claros centrados no beneficio do ser humano e a participação aberta dos usuários do sistema.
O discurso iluminista da exclusão digital : crítica do mundaneum informático pós-fordista de knoxville, tennessee
Keywords: Digital Divide; Information Society; Discourse; Exclusão Digital; Brecha Digital; Sociedade da Informação; Discurso